Dietary fibre intake and its associations with depressive symptoms in a prospective adolescent cohort. Issue 10 (28th May 2021) - Swann, Olivia G.; Breslin, Monique; Kilpatrick, Michelle; O'Sullivan, Therese A.; Mori, Trevor A.; Beilin, Lawrence J.; Lin, Ashleigh; Oddy, Wendy H.
Abstract: Depression is a major cause of disability in adolescents. Higher dietary fibre intake has been associated with lower depressive symptoms in adults, but there is a lack of research in adolescents. We examined the association between dietary fibre intake (Commonwealth Scientific and Industrial Research Organisation (CSIRO) FFQ) and depressive symptoms (Beck Depression Inventory for Youth) in adolescents with prospective data from the Raine Study Gen2 14- and 17-year follow-ups ( n 1260 and 653). Odds of moderate/extreme (clinically relevant) depressive symptoms by quartile of fibre intake were calculated using mixed-effects logistic regression for all participants, in a paired sample without moderate/extreme depressive symptoms at 14 years and in a sub-sample of participants with available inflammatory data at the ages of 14 and 17 years ( n 718 and 547). Odds of moderate/extreme depressive symptoms were lower in the fourth (highest) quartile of overall fibre intake (OR 0·273, 95 % CI 0·09, 0·81) compared with the first (lowest) quartile, adjusting for sex, age, energy intake, adiposity, and family and lifestyle factors. However, further adjustment for dietary patterns attenuated the results. Associations of depressive symptoms with cereal or fruit and vegetable fibre intake were not significant in the final model. Adjustment for inflammation had no effect on OR. The association between a higher dietary fibre intake and lower odds of clinically relevant depressive symptoms may be more reflective of a high-fibre diet with all its accompanying nutrients than of an independent effect of fibre.